Ten Years of Water Service Reform in Latin America : Toward an Anglo-French Model - Foster, Vivien (World Bank, Washington, DC, 2014)
During the 1990s, most countries in the Latin American region undertook major reforms of their water supply industries. Chile was the first to attempt to modernize its water sector with new legislation passed as early as 1988. By 1991, both Argentina and Mexico were beginning to conduct a series of experiments with private sector participation (PSP). In a second wave, Peru, Colombia, and Bolivia enacted ambitious new legislation in the mid-1990s, and during the second half of the decade, reform began to take root in Brazil and Central America. By the end of the 1990s, nearly all countries had completed reforms, had major reforms in process, or were actively considering reforms.